2015
DOI: 10.1177/0046958015601826
|View full text |Cite
|
Sign up to set email alerts
|

Provider Behavior Under Global Budgeting and Policy Responses

Abstract: Third-party payer systems are consistently associated with health care cost escalation. Taiwan’s single-payer, universal coverage National Health Insurance (NHI) adopted global budgeting (GB) to achieve cost control. This study captures ophthalmologists’ response to GB, specifically service volume changes and service substitution between low-revenue and high-revenue services following GB implementation, the subsequent Bureau of NHI policy response, and the policy impact. De-identified eye clinic claims data fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous studies have shown the underreporting of CT and MRI in US inpatient claims data [ 12 ], which may also occur in Taiwan. The NHI Bureau limits the reimbursement of multiple CT scans for a patient at the same day and imposes penalties for outliers in service volumes, leading to changes in provider behavior such as discretionary billing [ 13 ]. To observe this phenomenon, we compared the number of CT scans in claim records with total CT scans, including uncoded and self-pay scans, in our hospital during 2010–2017.…”
mentioning
confidence: 99%
“…Previous studies have shown the underreporting of CT and MRI in US inpatient claims data [ 12 ], which may also occur in Taiwan. The NHI Bureau limits the reimbursement of multiple CT scans for a patient at the same day and imposes penalties for outliers in service volumes, leading to changes in provider behavior such as discretionary billing [ 13 ]. To observe this phenomenon, we compared the number of CT scans in claim records with total CT scans, including uncoded and self-pay scans, in our hospital during 2010–2017.…”
mentioning
confidence: 99%